The Influence of Islamic Law with Tafsir Bi Al-Ma'tsur in Indonesia - Sri Ulfa Rahayu; Nurul Hartini; Fitria Ningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The sources of Islam are the Quran and the Hadith. However, when interpreting legal verses, not all use Tafsir Bi Al-Ma'tsur, which essentially means non-negotiable legal issues. The purpose of this study was to determine the application of Tafsir Bi Al-Ma'tsur in Indonesia, which was only applied to laws concerning marriage, religious courts, waqf (waqf), Islamic banking, and zakat. This research employed a qualitative method. The researcher consulted sources on Islamic law, the history of Islamic law in Indonesia, Tafsir Bi Al-Ma'tsur, and other related matters. The results of this study indicate that Islamic law with Tafsir Bi Al-Ma'tsur in Indonesia has not had much influence. The existing laws in Indonesia are influenced by colonial nations, and Indonesia is also a country with diverse ethnicities and religions. This is why Tafsir Bi Al-Ma'tsur has not had much influence on Indonesian law.